Studi Geodiversitas Pantai Dulanga Desa Bongo, Kecamatan Batudaa Pantai, Kabupaten Gorontalo - Usman, Miranda Melia; Arifin, Yayu Indriati; Kasim, Muhamad; Aris, Ayub Pratama (Journal of Applied Geoscience and Engineering, 2024)
In simple terms, geodiversity is defined as the diversity of non-living natural components in the form of lithology, minerals, fossils, structures and landforms in an area that forms the earth's surface which has differences, thus forming diversity. Geodiversity can be an important factor in developing the tourism industry and local community identity by conducting special research in the form of investigating geological heritage and cultural heritage and integrating the results for educational outcomes in education, promotion and tourism infrastructure. Gorontalo Province has many locations that show great geological diversity, but many of them have not been explored, studied, or not yet established for geotourism. The extraordinary geo-diversity together with the deep ecological resources and cultural heritage provides a valuable basis for the development of geotourism and geoparks. Geological research at Dulanga Beach has never been carried out to assess the existing geological features. Research on Dulanga Beach generally only focuses on the tourism promotion sector. The aim of this research is to determine the potential geodiversity potential of Dulanga Beach. The method used in this research is the main method, namely geological observation and geodiversity assessment methods. Based on research results, the Dulanga beach location has 3 geological features in the form of geomorphology, lithology and fossils or paleontology. The results of the geodiversity assessment show that the Dulanga Beach research for the Scientific Assessment aspect is in the Moderate class, the Educational Assessment is in the High class, the Tourism Assessment is in the Moderate class, and the Assessment Degradation (Degradation Value) is included in the High class.